2016
DOI: 10.1186/s12883-016-0771-4
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in patients with multiple sclerosis, hereditary ataxia or hereditary spastic paraplegia after at least 10 years of disease - a case control study

Abstract: BackgroundAlthough disability is considered the main cause of low bone mineral density (BMD) in multiple sclerosis (MS), other factors related to the disease process or treatment could also be involved. The aim of this study was to assess whether patients with MS are more likely to develop low BMD (osteopenia or osteoporosis) than patients with the non-inflammatory neurological diseases Hereditary Spastic Paraplegia (HSP) and Hereditary Ataxia (HA).MethodsWe performed a case control study comparing BMD (spine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…However, disabling neurological diseases like spinocerebellar degeneration or multiple sclerosis, which are similar to MSA, are considered to have likely low BMD and high fracture incidence. 3 , 4 Thus, osteoporosis and bone health should be considered in all patients with both inflammatory and degenerative chronic neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, disabling neurological diseases like spinocerebellar degeneration or multiple sclerosis, which are similar to MSA, are considered to have likely low BMD and high fracture incidence. 3 , 4 Thus, osteoporosis and bone health should be considered in all patients with both inflammatory and degenerative chronic neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In a case-control study examining the association between MS and likelihood of developing osteopenia or osteoporosis, a total of 91 men ( n = 45) and women ( n = 46) with MS (mean [SD] age: 52.0 [10.3] years) had a total body bone mineral density of 1.12 g/cm 2 and T-score of −0.6, indicating total bone density was not in the range of osteopenia or osteoporosis according to the World Health Organization classification. However, patients with MS in this analysis had bone density in the lumbar spine (bone density: 1.07 g/cm 2 ; T-score: −1.09) and the left femoral hip (bone density: 0.69–0.86 g/cm 2 ; T-score: −1.43 to −1.56) indicative of osteopenia, suggesting bone loss may be more prominent in certain areas of the body among MS patients ( 56 ). The North American Menopause Society recommends bone mineral density be tested in postmenopausal women who are at a higher risk of osteoporosis due to medical conditions, such as MS, and provides guidance for pharmaceutical management strategies ( 61 ).…”
Section: Clinical Assessment and Care Of Women With Msmentioning
confidence: 86%
“…In all women, the risk of osteoporosis and related fractures increases post menopause ( 53 , 54 ). However, osteoporosis is more common in patients with MS compared with healthy populations; bone loss starts early during MS disease course, and increases as the disease progresses ( 55 , 56 ). Moreover, there is evidence showing that chronic use of glucocorticosteroids reduces bone formation and is a risk factor for osteoporotic fractures ( 57 ), although data from studies in MS patients are conflicting ( 58 60 ).…”
Section: Clinical Assessment and Care Of Women With Msmentioning
confidence: 99%
“…This study also found a correlation between CAG expansion and low femoral neck score, providing further evidence that gene alterations may be related to lower BMD. Simonsen et al found that 75.3% of patients with hereditary ataxia had osteopenia or osteoporosis (Simonsen et al, 2016). These studies suggest the need for routine BMD measurements in ataxia patients to initiate prophylactic osteoporosis treatments.…”
Section: Ataxiamentioning
confidence: 99%